Diabetes Awareness and Dietary Habits of Non-Diabetic Females in Private Universities in Jeddah Saudi Arabia - Hakim, Noor (Progress in Nutrition, 2021)
Objective:The study aims to investigate the level of awareness among non-diabetes female students towards the diabetes disease and its association with dietary habit. ResearchMethods and Procedures:A total of 141 female students with high socioeconomic status has been recruited from private universities in the city of Jeddah. The knowledge level of selected participants has been assessed by answering short test about diabetes information. Dietary habit and related anthropometric measurements were examined. Results:Non-diabetic students majoring in non-medical field had good background of diabetic disease (average test score was 11.4 out of 15) specially in the disease symptoms and some of the protective factors. However, they are weak in the pathological detailsof the disease. Majority of the students (77.3%) understood the protective factors of eating fruit and vegetables; however, they are far away from the recommendation intake and were not significantly associated with DM awareness score. Moreover, majority of participants reported a limited consumption of fried or fat-foods and sugary drinks, ranging between never to a few times per week (73.4% and 68.8%, respectively). The mean knowledge regarding Diabetes Mellitus (DM) at the different frequencies of sugary drink intakes was significantly different (F=2.97; p-value=0.014). Scheffe test revealed no statistically significant difference between the groups, where all the significant levels were greater than 0.05. Conclusions:Medical and healthy educational sessions such as the pathology of the diabetes disease, healthy eating habit seminars, and workshops are recommended to increase non-medical field student’s awareness.